Study of prescribing pattern of drugs in the management of migraine with psychiatric comorbidities at integral institute of medical science and research - Mustapha, Abubakar; Khan, Kamran; Yusuf, Mantasha; Abbas, Amir; Sada, Mudassir; Badruddeen; Ajmal, M. Yasir; Farooaqui, Azhar Mahmood (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Migraine headaches, a prevalent and serious brain condition, often coincide with mental health issues. This study aims to explore drug prescribing patterns for migraine patients with psychiatric comorbidities. Methods: Over six months, a prospective observational study was conducted at the psychiatric department of IIMS&R Hospital. 100 prescriptions were analyzed based on specific criteria. Results: Total 14 different drugs were prescribed. NSAIDs were most common (87%), followed by multivitamins (50%), benzodiazepines (30%), and tricyclic antidepressants (23%).Naxdom (NSAIDs) was frequently used (87%). Patients aged 31-45 years had higher prevalence. Comorbidities associated are depression (18%), anxiety disorder (10%), insomnia (5%). Conclusions: The study highlights various orally administered drugs, including anti-migraine meds, antidepressants, anticonvulsants, and more. Patients within the 31-45years age group were significantly affected. Migraine correlated with depression, anxiety, and insomnia. The most common medication was naxdom 250mg taken orally.